Enhancing Students’ Procedural Writing Skills through Chain Writing Technique: A Classroom Action Research - Serihartati Serihartati; Ari Purnawan (Journal of Innovation and Research in Primary Education, 2026)
Writing procedural texts remains a challenging task for English as a Foreign Language (EFL) learners, particularly at the junior high school level, due to difficulties in organizing ideas, applying appropriate language features, and maintaining engagement in the writing process. While collaborative writing strategies have been widely studied, limited research has examined the use of the chain writing technique within a Classroom Action Research (CAR) framework to address genre-specific writing problems in authentic classroom contexts. This study aimed to enhance EFL students' procedural writing skills by implementing the chain writing technique using a CAR design. Conducted with 32 eighth-grade students at an Indonesian junior high school, the research involved two instructional cycles: planning, action, observation, and reflection. A mixed-methods approach was employed, combining writing tests with classroom observations, questionnaires, and interviews. The findings indicate substantial improvement in students' procedural writing performance across cycles, along with increased engagement, collaboration, and confidence in writing activities. The study highlights the effectiveness of chain writing as a collaborative strategy and demonstrates the added value of CAR in enabling iterative instructional refinement based on students' learning responses. The novelty of this study lies in integrating the chain writing technique into a cyclical CAR framework to improve procedural writing as a specific genre in a junior high school EFL context.